SAPAAN DI LINGKUNGAN BATALYON INFANTERI 403 YOGYAKARTA (STUDI KASUS) - , Fauzia ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Addressing each other or addressing activity among the members of community or society happens when there is a person makes a communication with other people. Addressing words used depend on the relationship between the speaker and the interlocutor. Addressing each other could be seen in battalion infantry 403 (BI 403) of Yogyakarta. The aims of this research are to describe: (a) the addressing form at battalion infantry 403 Yogyakarta, (b) the classification of addressing form at battalion infantry 403 Yogyakarta, (c) the functions of addressing form at battalion infantry 403 Yogyakarta, and (d) the factors which influence the variation for the use of addressing form at battalion infantry 403 Yogyakarta. Data is collected by searching as many as possible data which has any correlation with the research theme. It uses interview and attentive observation attentively namely listening to the use of the language. Data is also collected by observing interaction among the members of battalion. On the data analysis, the data which has found then is firstly classified based on the structure of the language using âpadan intralingualâ method. The data, then, is further analyzed using âpadan extralingualâ. It is a method that is used to analyze the correlation between elements of the language with the elements outside of the language influencing the choice of terms of address used by the speaker, it is SPEAKING. The first classification is based on form. Based on the form, addressing form at battalion infantry 403 Yogyakarta can be divided into addressing form in the form of word and phrase. The classification based on word can be divided into two that are base form and derived form. The derived form that has got through morpheme process can be divided into addressing form which comes from reduplication and abbreviation process. Next, the classification of addressing form based on syntax distribution, it can be divided into addressing form in the beginning of the clause and in the end of the clause. The classification of addressing form at battalion infantry 403 based on the meaning can be divided into five categories. They are: rank term, function/duty term, code term, proper name term, and kinship term. The function of addressing form at battalion infantry 403 Yogyakarta can be divided into four. They are the addressing form from the higher to the subordinate, the subordinate to the higher, the all soldiers in the same level and addressing form which is used in the family relationship. The important factors to establish the choice of address used by the speaker are setting, participant, end, and instrument.